Vestibulo-ocular reflex and motion sickness in figure skaters - Tanguy, S.; Quarck, G.; Etard, O.; Gauthier, A.; Denise, P. (European Journal of Applied Physiology, 2008)
In order to determine the effect of figure skating on the functional plasticity of the vestibular system, we quantified vestibulo-ocular reflex (VOR) and motion sickness (MS) intensity in 11 female figure skaters and 11 matched control subjects. Vestibular stimulation consisted of three cycles of sinusoidal rotation (0.025 Hz, ±60°/s) and two velocity steps of 60°/s (acceleration 60°/s2). Nauseogenic stimulation consisted of a constant velocity (60°/s) off vertical axis rotation (OVAR) using a 15° tilt angle. Subjective sickness symptoms were rated immediately after OVAR with the Pensacola diagnostic index. During sinusoidal stimulations, the skaters` VOR, as compared with that of the controls, demonstrates a gain that is 27% lower (0.44± 0.12 vs. 0.58 ± 0.10; P < 0.01) and a phase advance (10 ± 12° vs. -0.3 ± 6.4°; P < 0.05). During velocity steps, the VOR gain is 32% lower among the skaters (0.52 ± 0.14 vs. 0.71 ± 0.12; P < 0.01), but there is no difference in time constant (10.8± 1.8 s vs. 10.5 ± 2.7 s; P = 0.78). Nauseogenic stimulation evokes significantly less MS in figure skaters than in control subjects (2.8 ± 2.8 vs. 16.2 ± 13.7; P < 0.01). Quantitative alterations in VOR parameters observed in figure skaters probably result from vestibular habituation induced by repeated unusual stimulations when practicing figure skating.